2007
DOI: 10.1021/jm061280h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery ofN-(4-(3-Amino-1H-indazol-4-yl)phenyl)-N‘-(2-fluoro-5-methylphenyl)urea (ABT-869), a 3-Aminoindazole-Based Orally Active Multitargeted Receptor Tyrosine Kinase Inhibitor

Abstract: In our continued efforts to search for potent and novel receptor tyrosine kinase (RTK) inhibitors as potential anticancer agents, we discovered, through a structure-based design, that 3-aminoindazole could serve as an efficient hinge-binding template for kinase inhibitors. By incorporating an N,N'-diaryl urea moiety at the C4-position of 3-aminodazole, a series of RTK inhibitors were generated, which potently inhibited the tyrosine kinase activity of the vascular endothelial growth factor receptor and the plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(98 citation statements)
references
References 21 publications
1
96
0
1
Order By: Relevance
“…ABT-869 is an oral potent TKI inhibitor of VEGFR-1, VEGFR-2, VEGFR-3, PDGFRß, and Flt3 [99,100]. Data suggests ABT-869 is more selective toward VEGFR and PDGFR than other similar TKIs while also having apoptotic effects [101].…”
Section: Abt-869mentioning
confidence: 99%
“…ABT-869 is an oral potent TKI inhibitor of VEGFR-1, VEGFR-2, VEGFR-3, PDGFRß, and Flt3 [99,100]. Data suggests ABT-869 is more selective toward VEGFR and PDGFR than other similar TKIs while also having apoptotic effects [101].…”
Section: Abt-869mentioning
confidence: 99%
“…Furthermore, mangiferin was tested against ALK, insulin receptor, and EGFR, for kinase selectivity and found to inhibit ALK activity with an IC 50 value of 0.8 μM, whereas it was found inactive against insulin receptor (> 10 μM), and EGFR (> 10 μM; Table 1). As described elsewhere 6,8,9 , small-molecule FLT3 inhibitors in clinical development, midostaurin, lestaurtinib, tandutinib and linifanib, are known to target multityrosine kinase. This xanthone used in the current study was also found to display a non-selective inhibitory effect against FLT3 and ALK.…”
Section: In Vitro Kinase Assaymentioning
confidence: 99%
“…Due to their structural novelty and important biological activities, the synthesis of complex chiral molecules around a biologically relevant framework has played an important role in the discovery of drugs 14 . Furthermore, some 2-phenylbenzofuran analogues have showed potent anticancer activities [15][16][17] . The [4 + 2] cycloaddition between N-arylimines and electron-rich alkenes, the multicomponent Povarov reaction has been catalyzed by various lewis acid catalysts, such as I 2 , InCl 3 , TFA and p-TsOH [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%